2009
DOI: 10.1016/j.catena.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Research on the SCS-CN initial abstraction ratio using rainfall-runoff event analysis in the Three Gorges Area, China

Abstract: a b s t r a c t a r t i c l e i n f oThe Soil Conservation Service Curve Number (SCS-CN) method is widely used for predicting direct runoff from rainfall. The ratio of initial abstraction (Ia) to maximum potential retention (S) was assumed in its original development to be equal to 0.2 in SCS-CN method. The constant initial abstraction ratio is the most ambiguous assumption and requires considerable refinement. The objectives of this study were (1) to determine the initial abstraction ratio, in an experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(112 citation statements)
references
References 22 publications
10
92
0
10
Order By: Relevance
“…Fu et al (2011) found that the prediction accuracy for λ = 0.05 was greater than that for λ = 0.2 using SCS-CN method to simulate plot runoff of 757 rainfall events in Zizhou and Xifeng cities located in the Loess Plateau of China. Similar results have been obtained from plots or watersheds in USA (Hawkins et al, 2002), semi-arid tropical highlands of northern Ethiopia (Descheemaeker et al, 2008) and the Three Gorges area of China (Shi et al, 2009). In this study, the value of λ is not optimized using the measured rainfall-runoff data, as optimization of parameters cannot adequately examine the applicability of the modified SCS-CN model.…”
Section: Parameters For Rainfall-runoff Modelingsupporting
confidence: 67%
See 1 more Smart Citation
“…Fu et al (2011) found that the prediction accuracy for λ = 0.05 was greater than that for λ = 0.2 using SCS-CN method to simulate plot runoff of 757 rainfall events in Zizhou and Xifeng cities located in the Loess Plateau of China. Similar results have been obtained from plots or watersheds in USA (Hawkins et al, 2002), semi-arid tropical highlands of northern Ethiopia (Descheemaeker et al, 2008) and the Three Gorges area of China (Shi et al, 2009). In this study, the value of λ is not optimized using the measured rainfall-runoff data, as optimization of parameters cannot adequately examine the applicability of the modified SCS-CN model.…”
Section: Parameters For Rainfall-runoff Modelingsupporting
confidence: 67%
“…Firstly, rainfall intensity and rainfall duration have great impact on the quantity of runoff, but they were not considered in the modified SCS-CN model. More efforts are needed to account for the temporal variation of rainfall, such as done in Mishra et al (2008) and Suresh Babu and Mishra (2012). Secondly, it is difficult to independently determine the introduced empirical coefficients in the modified RUSLE model.…”
Section: Discussion Of the Proposed Approachmentioning
confidence: 99%
“…There have been studies (Shi et al, 2009;Woodward et al, 2003) that 10 tried to determine I a from hydrographs. A problem with this approach is that there can be a time lag between runoff generation in headwaters and its detection at gauging station.…”
Section: Problems With the Current Usage Of Iamentioning
confidence: 99%
“…Conversely, when λ W decreases, storage is transferred from 5 I a to S. This is important because several studies (Baltas et al, 2007;D'Asaro and Grillone, 2012;Shi et al, 2009;Woodward et al, 2003) found that the optimal value of λ W was much less than 0.2, and even close to zero in many watersheds. This shows that there is a positive correlation between a decrease in λ W , storage transfer from I a to S, and a general increase in model performance for the reasons mentioned above.…”
mentioning
confidence: 99%
“…The initial abstraction coefficient typically varies from 0.0 to 0.2 [19,20]. The CN tables published and currently used typically assume that the initial abstraction coefficient is 0.2.…”
Section: Introductionmentioning
confidence: 99%